An allosteric gating model recapitulates the biophysical properties of IK, L expressed in mouse vestibular type I hair cells. (24th September 2017) - Spaiardi, Paolo; Tavazzani, Elisa; Manca, Marco; Milesi, Veronica; Russo, Giancarlo; Prigioni, Ivo; Marcotti, Walter; Magistretti, Jacopo; Masetto, Sergio
Abstract : Key points: Vestibular type I and type II hair cells and their afferent fibres send information to the brain regarding the position and movement of the head. The characteristic feature of type I hair cells is the expression of a low‐voltage‐activated outward rectifying K + current, I K, L, whose biophysical properties and molecular identity are still largely unknown. In vitro, the afferent nerve calyx surrounding type I hair cells causes unstable intercellular K + concentrations, altering the biophysical properties of I K, L . We found that in the absence of the calyx, I K, L in type I hair cells exhibited unique biophysical activation properties, which were faithfully reproduced by an allosteric channel gating scheme. These results form the basis for a molecular and pharmacological identification of I K, L . Abstract: Type I and type II hair cells are the sensory receptors of the mammalian vestibular epithelia. Type I hair cells are characterized by their basolateral membrane being enveloped in a single large afferent nerve terminal, named the calyx, and by the expression of a low‐voltage‐activated outward rectifying K + current, I K, L . The biophysical properties and molecular profile of I K, L are still largely unknown. By using the patch‐clamp whole‐cell technique, we examined the voltage‐ and time‐dependent properties of I K, L in type I hair cells of the mouse semicircular canal. We found that the biophysical properties of I K, L were affected by an unstable K + equilibrium potential ( V eq K + ). Both the outward and inward K + currents shifted V eq K + consistent with K + accumulation or depletion, respectively, in the extracellular space, which we attributed to a residual calyx attached to the basolateral membrane of the hair cells. We therefore optimized the hair cell dissociation protocol in order to isolate mature type I hair cells without their calyx. In these cells, the uncontaminated I K, L showed a half‐activation at –79.6 mV and a steep voltage dependence (2.8 mV). I K, L also showed complex activation and deactivation kinetics, which we faithfully reproduced by an allosteric channel gating scheme where the channel is able to open from all (five) closed states. The 'early' open states substantially contribute to I K, L activation at negative voltages. This study provides the first complete description of the 'native' biophysical properties of I K, L in adult mouse vestibular type I hair cells. Key points: Vestibular type I and type II hair cells and their afferent fibres send information to the brain regarding the position and movement of the head. The characteristic feature of type I hair cells is the expression of a low‐voltage‐activated outward rectifying K + current, I K, L, whose biophysical properties and molecular identity are still largely unknown. In vitro, the afferent nerve calyx surrounding type I hair cells causes unstable intercellular K + concentrations, altering the biophysical properties of I K, L . We found that in the absence of the calyx, I K, L in type I hair cells exhibited unique biophysical activation properties, which were faithfully reproduced by an allosteric channel gating scheme. These results form the basis for a molecular and pharmacological identification of I K, L .